Evaluation of a Community Social Responsibility (CSR) Program Based on a Community Satisfaction Index: A Case Study of the Kasih Bumi and Ruang Tumbuh Kalisogo Programs at PT Perusahaan Gas Negara OMM Region III - Purwanto, Wahyu; Nur Mashitohiyah; Faiz Salman Ar-rosyid (Indonesian Journal of Social Responsibility Review (IJSRR), 2025)
Abstract This study aims to measure and analyze the level of Community Satisfaction Index (CSI) among beneficiaries of the Corporate Social Responsibility (CSR) programs—KASIH BUMI and Ruang Tumbuh Kalisogo—organized by PT Perusahaan Gas Negara (PGN) OMM Region III in Sidoarjo Regency, East Java. The method employed is census (saturated sampling), with the CSI calculated using the weighted average value formula. The overall CSI result showed a value of 3.78 (Converted Value: 94.5), which places the program's performance in the "Very Good" category (Service Quality A).Out of ten assessment elements, nine elements (such as Requirements, Procedures, Implementation Time, and Environmental Impact) were found to be in the "Very Good" category. However, the element with the lowest score was the Economic Impact (U8), with a score of 3.39 (Converted Value: 84.75), which is categorized as "Good."In conclusion, although the CSR program of PT PGN OMM Region III has generally achieved a 'Very Good' satisfaction level (CSI 94.38), the indicator analysis reveals that the Economic Impact dimension still requires improvement. The program needs to enhance concrete and sustainable economic benefits for the beneficiaries.